EFFECT OF THE APPLICATION OF ARTIFICIAL INTELLIGENCE (AI) AND AUDITOR COMPETENCIES ON AUDIT QUALITY AT PUBLIC ACCOUNTING FIRMS IN WEST JAVA - Iendy Cinta Maharani; Moh Yudi Mahadianto (CV. Radja Publika, 2026)
This study aims to analyze the influence of the implementation of Artificial Intelligence (AI) and auditor competencies on audit quality at Public Accounting Firms (PAFs) in West Java. This study employs a quantitative approach using primary data collected via a questionnaire measured on a 1–5 Likert scale. The population of this study consists of auditors working at Public Accounting Firms in West Java. The sample was determined using non-probability purposive sampling, resulting in 128 auditor respondents. Data analysis was conducted using Partial Least Squares-based Structural Equation Modeling (SEM-PLS). The results indicate that the implementation of Artificial Intelligence (AI) has a positive and significant effect on audit quality. Furthermore, auditor competence also has a positive and significant influence on audit quality. These findings suggest that the integration of AI technology, supported by adequate auditor competence, can improve audit quality at Public Accounting Firms